PENGARUH HARGA DAN IKLAN TERADAP MINAT PEMBELIAN PADA PRODUK KRATINGDENG (Studi Pada PT. Arta Boga Cemerlang) - Juang Ade Sulung; Sri Wahyuni Mega; Lina Saptaria (CV SWA Anugrah, 2023)
This research aims to determine the influence of price and advertising on purchasing interest at PT. Arta Boga Cemerlang. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to PT retailers. Arta Boga Cemerlang and calculated using the SPSS Version 25 application. The population in this study was all kratingdeng product retailers totaling 80 people and the sample was part of the retailers totaling 67 people. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t Test, F Test, and R2 Coefficient of Determination Test. In the Validity Test, it is known that all question items (X1, X2, and Y) have a significance value of 0.000 < 0.05 so that each variable is declared valid. Then in the Reliability Test each variable was declared reliable because it had a Cronbach's Aplha value > 0.60. Then in the t test it is known that the price (X1) and advertising (X2) variables have a significance value of 0.000 < 0.05 so that these two variables partially have a significant effect on purchase intention. Then the F test shows that the significance value is 0.000 <0.05, which shows that price and advertising have a simultaneous effect on purchasing interest at PT. Artha Boga Cemerlang.